The Concept of Racism in Morrison's " Song of Solomon" (مجلة ديالى للبحوث الانسانية, 2016)
Toni Morrison's third novel Song of Solomon, establishes her as a major African- American writer. The story of a black man's research for  his identity, through a discovery of his family history, became a best seller and drew praise from readers and critics, when it was published in (1977). The novel has been especially admired for the beauty of language and its grounding of universal theme in particularity of the African American experiences, as well as for its use of folklore.     Song of Solomon is based on an African- American folktale about slaves who can fly to Africa when they choose. Morrison fictionalizes this folktale through the character of Solomon, the great-grandfather of the story's protagonist, Milkman Dead. Through his discovery of the story of Solomon and his ability to fly, Milkman learns to take pride in his ancestry and to value his connection to family and community.Song of Solomon won the National Book Critics Circle Award for fiction. It is now widely taught, and appeared again on the best seller lists when it was chosen by Oprah Winfrey for inclusion in her book club and it is still considered one of Morrison's best books.